Dari Barter sampai Monopoli: Perdagangan Cendana dan Pengaruh Eropa di Wilayah Timor Barat Abad Ke-18 - Jeff Wilfred Mesah (Historia Madania: Jurnal Ilmu Sejarah, 2022)
The aroma of Timor sandalwood has attracted many traders from Asia and Europe to come to this region to get it. Because of its very high profit and selling value, Europeans began to compete to obtain large amounts of sandalwood. Therefore, the purpose of reconstructing the historical processes that occur related to this theme is very important to be exposed. So the question arises: How was the influence and dominance of Europeans about the sandalwood trading in West Timor in the 18th century? In order to obtain answers, the critical historical method is used as well as the use of primary and secondary sources and the study of relevant references. Thus, it is a fact that, with the increasingly bustling sandalwood trade, Timor is included in the world trade network. But on the other hand, it caused discord among Europeans. Each of them instills influence and dominance in order to control this sandalwood-producing area. So the Europeans implemented a political intervention aimed on the economical monopoly, because sandalwood which was originally a trading commodity for the local community was then controlled by European powers. The result of this dispute was the division of the island of Timor into two parts.